1996
DOI: 10.1046/j.1365-2346.1996.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of ascorbic acid and xylitol in etomidate-induced adrenocortical suppression in humans

Abstract: Etomidate-induced suppression of cortisol biosynthesis is a result of a blockade of 11-beta-hydroxylation in the adrenal gland, mediated by the imidazol radical of etomidate. Since the generation of steroids requires reductive and energy rich equivalents, the present study examined whether supplementation with ascorbic acid or xylitol, a major source of NADPH, could attenuate adrenal suppression by etomidate in human subjects by promoting the turnover rate of 11-beta-hydroxylase. During continuous etomidate/al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Other studies showed no evidence of a clinically relevant attenuating effect of ascorbic acid or xylitol on etomidate-induced adrenocortical suppression. [ 16 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed no evidence of a clinically relevant attenuating effect of ascorbic acid or xylitol on etomidate-induced adrenocortical suppression. [ 16 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…The studies concerning the effects of AA and etomidate on stress response were varying in terms of chosen method and parameters; moreover, they were contradictory (4–8). Besides, it has been declared that the stress response is directly proportional to the severity of surgical trauma and that the body may give higher endocrinal and metabolic response to intra‐abdominal operations than superficial body operations (9).…”
Section: Discussionmentioning
confidence: 99%
“…Schaag et al . (7) reported that, during the anaesthesia provided by etomidate plus alfentanil infusion, no significant change in cortisol levels has been observed in the patients who were given or not given 0.5 g/h AA, but it has been implied that AA given before anaesthesia brings cortisol to normal levels (8).…”
Section: Discussionmentioning
confidence: 99%
“…70 A new agent, dexmedetomidine, which produces sedation without respiratory depression, has been approved for use in adults and may have a role in the care of these patients. 71,72 Propofol should be used with caution or avoided entirely in children with recognized asthma. Recently released generic preparations of this agent contain high concentrations of sulfites, which can precipitate severe bronchospasm in susceptible individuals.…”
Section: Respiratory Problemsmentioning
confidence: 99%
“…This effect is generally clinically insignificant when given as a single dose in normal patients but should probably be avoided in children with an abnormal adrenal-pituitary axis. 71,72 Children with metabolic problems or inborn errors of metabolism can present difficulties with drug selections. 73 Complications can occur with both the medications themselves as well as with their metabolism rates and metabolites.…”
Section: Endocrine/metabolic Problemsmentioning
confidence: 99%